Understanding of failure and failure of understanding: Aspects of failure in the Old Testament - James Alfred Loader (HTS Teologiese Studies/Theological Studies, 2014)
Taking its cue from Rudolf Bultmann’s famous verdict that the Old Testament is a ‘failure’ (‘Scheitern’), the article reviews three influential negative readings of Israel’s history as told in the Former Prophets. It is then argued that awareness of the theological problem posed by Israel’s history enabled the redactors of both the former and the latter prophetic collections to deal with the element of human failure in a way that facilitated Israel’s retaining of her faith. Next, the sapiential insight in failing human discernment is drawn into the equation. Failure of human action is here interrelated with failure to comprehend God’s order. By virtue of its incorporation into the totality of the Tanak, this insight became a constructive part of Israel’s faith. Therefore the concept of failure comprises more than coming to terms with Israel’s catastrophic history. Since it is encoded in Israel’s Holy Scripture, ‘failure’ is a major concept within the Old Testament internally and is therefore not suitable as a verdict over the Old Testament by an external value judgement. ‘Failure’ thus becomes a key hermeneutical category, not merely so that the Old Testament could become a ‘promise’ for the New Testament to fulfil, but as a manifestation of limits in human religion and thought. Far from undermining self-esteem, constructive use of the concept of her own failure sustained Israel in her catastrophe and should be adopted by Christianity – not least in South Africa, where the biblical message was often misappropriated to bolster apartheid.